2019
DOI: 10.1016/j.tmaid.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of Blastocystis spp. in travellers - A prospective longitudinal study

Abstract: This study shows that Blastocystis carriage in travellers is highly dynamic. The observed acquisition and loss of Blastocystis could either be travel-related or reflect the natural course of Blastocystis carriage. We demonstrate that the majority of Blastocystis detected in post-travel samples were already carried before travel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…S2 ). In agreement with recent studies ( 36 , 37 ), we observed that a total of 30% of healthy subjects were colonized by the anaerobic gut protozoon Blastocystis hominis or Dientamoeba fragilis , yet these protozoa were undetectable following antibiotic administration ( Table S2 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S2 ). In agreement with recent studies ( 36 , 37 ), we observed that a total of 30% of healthy subjects were colonized by the anaerobic gut protozoon Blastocystis hominis or Dientamoeba fragilis , yet these protozoa were undetectable following antibiotic administration ( Table S2 ).…”
Section: Resultssupporting
confidence: 92%
“…Phocine herpesvirus (PhoHV) DNA was added to all samples as an internal control for extraction and amplification efficiency. The presence of Giardia lamblia , Cryptosporidium parvum , Entamoeba histolytica , Blastocystis hominis , and Dientamoeba fragilis was assessed by real-time PCR targeting the small-subunit rRNA gene ( 37 ). Positive controls consisting of a plasmid containing the target sequence were included in every run, as were negative extraction controls and negative PCR controls.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies report a significant higher occurrence of ST1 in individuals traveling outside of Europe (Bart et al, 2013 ; Rudzińska et al, 2019 ), however, we found no such correlation. Traveling outside the Europe is also often correlated with the occurrence of “avian” subtypes ST6 and ST7 (e.g., Rudzińska et al, 2019 ; van Hattem et al, 2019 ), but we did not confirm this.…”
Section: Discussioncontrasting
confidence: 73%
“…in 15.3% of Polish military personnel returning from peacekeeping missions in Iraq and Afghanistan. A prospective, multi-center COMBAT study among Dutch travelers in 2001 [ 85 ] showed Blastocystis spp. infection in 36.3% of subjects.…”
Section: Discussionmentioning
confidence: 99%